The Theory of Consent Vices in Terms of the Rules of Consumer Law through European Legislation - Olesea PLOTNIC (Eastern European Journal of Regional Studies, 2020)
The balance of the consumer contract concerns more the notion of cause of the obligation, since the contractual balance supposes an analysis of the counterparties. Jurisprudence and doctrine have sometimes used this concept to remedy imbalances, in particular by carrying out a more global analysis of the content of the contract. Common law has its own rules for rebalancing the contract, and in particular the theory of vices of consent. The interest of this article is to show if the rules of common law can be used to balance the consumer contract and to what extent they are to fight against contractual unfair terms in consumer contracts.